2020
DOI: 10.5194/cp-16-2125-2020
|View full text |Cite
|
Sign up to set email alerts
|

Central Europe, 1531–1540 CE: The driest summer decade of the past five centuries?

Abstract: Abstract. Based on three drought indices (SPI, SPEI, Z-index) reconstructed from documentary evidence and instrumental records, the summers of 1531–1540 were identified as the driest summer decade during the 1501–2015 period in the Czech Lands. Based on documentary data, extended from the Czech scale to central Europe, dry patterns of various intensities (represented, for example, by dry spells, low numbers of precipitation days, very low rivers, and drying-out of water sources) occurred in 1532, 1534–1536, 15… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…The use of historical data in paleostudies has enjoyed a growing interest in past decades providing a more accurate understanding of the past climate variability (Brázdil et al, 2020). Climate changes in the past were often diachronic and significantly different at different locations (Martel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of historical data in paleostudies has enjoyed a growing interest in past decades providing a more accurate understanding of the past climate variability (Brázdil et al, 2020). Climate changes in the past were often diachronic and significantly different at different locations (Martel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A 3-year period, AD 1472-1474, can be considered a long dry period, peaking with the megadrought in AD 1473, which occurred in almost the whole of Europe. The period before AD 1540, when one of the most severe droughts in Europe occurred, can be considered unusually dry (Brázdil et al, 2020). Dry years were more prevalent in the 1580s, with extreme drought in AD 1590 and in the beginning of the 1680s.…”
Section: Droughts In the Suwałki Region Based On Historical Datamentioning
confidence: 99%
“…The driest summer decade of the past five centuries? (Brázdil et al, 2020). As we see it, our study should possibly be treated…”
Section: Introductionmentioning
confidence: 84%
“…A direct inspiration for this study can be found in the article published in 2020 in the "Climate of the Past" entitled Central Europe, 1531−1540 CE:The driest summer decade of the past five centuries? (Brázdil et al, 2020). As we see it, our study should possibly be treated…”
mentioning
confidence: 84%
“…This drought was probably the most severe in Central Europe for centuries, perhaps even for more than two millennia (Büntgen et al 2021 ). One has to go back to the first half of the sixteenth century to find heat and drought of comparable magnitudes in this region (Brázdil et al 2020 ; Büntgen et al 2021 ; Orth et al 2016 ; Wetter et al 2014 ). In 2022, large parts of Europe experienced yet another exceptional drought, but our analysis focuses on the years 2018–2020 owing to the lagged availability of socio-economic data.…”
Section: Introductionmentioning
confidence: 99%